Peripheral and Central Nervous System Immune Response Crosstalk in Amyotrophic Lateral Sclerosis - Liu, Zhouyang; Cheng, Xi; Zhong, Shanshan; Zhang, Xiuchun; Liu, Chang; Liu, Fangxi; Zhao, Chuansheng (Frontiers in Neuroscience, 2020)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease characterized by muscle weakness due to the degeneration of the upper and lower motor neurons. Neuroinflammation is known as a prominent pathological feature of ALS. Although neuroinflammation cannot trigger ALS, activated central nervous system (CNS) microglia and astrocytes, proinflammatory periphery monocytes/macrophages and T lymphocytes, and infiltrated monocytes/macrophages and T lymphocytes, as well as the immunoreactive molecules they release, are closely related to disease progression. The crosstalk between the peripheral and CNS immune components mentioned above significantly correlates with survival in patients with ALS. This review provides an update on the role of this crosstalk between the CNS and peripheral immune responses in ALS. Additionally, we discuss changes in the composition of gut microbiota because these can directly or indirectly influence this crosstalk. These recent advances may well provide innovative ways for targeting the molecules associated with this crosstalk and breaking the current treatment impasse in ALS.